PENERAPAN METODE FUZZY LOGIC DALAM MELAKUKAN PENILAIAN KINERJA GURU PADA SEKOLAH DASAR ISLAM TERPADU (SDIT) I’QRO - Siti Masripah (Paradigma, 2011)
Teachers are "professional educators with the primary task of educating, evaluating, guiding, directing, train, assess, and evaluate students on early childhood education formal education, primary education and secondary education. Performance appraisals of teachers conducted every month, and for the purpose of providing awards to teachers who have good work performance is in the form of bonuses and certain points and can be used for reference when the leadership will promote teachers to the specific position. Qualitative assessment of the employee's performance or teacher led assessments become uncertain, and the rules of the performance appraisal variables that can not be defined and thus require a method that can learn about the patterns of employee performance appraisal. Thus, in this study required a method or more used as a tool in determining the performance of the work of teachers, so it will be easier for the school in determining employee achievement and deserves the award. Key word: Performance, Assessment Teacher, Fuzzy Logic